NEW MEDIA DAN ETIKA KOMUNIKASI DIGITAL (UPAYA MENINJAU PRINSIP TANGGUNGJAWAB HANS JONAS) - A.A. Putra Dwipayana; Ni Putu Evi Setiawati (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2022)
The strong intensity of the development of communication technology does not necessarily have an impact on human life. The various symptoms that arise are the consequences behind the massive use of communication technology known as new media. On that basis, the importance of digital communication ethics needs to get an important position to provide orientation to individuals related to their responsibilities in life. The principle of responsibility of Hans Jonas is the focus of attention to observe this issue. This study is a qualitative study with a literature study approach. Based on the results of this study, the ethical principles of Jonas' responsibility are important to understand in relation to communication ethics in the massive digital space to strengthen human existence in responding to digital developments.Keywords: New Media, Digital Communication Ethics, Responsibilities of Hans Jonas